Diffusion of oxygen in Ti-15Mo-xZr alloys studied by anelastic spectroscopy - Vicente, Fábio Bossoi [UNESP]; Grandini, Carlos Roberto [UNESP] (Trans Tech Publications, 2014)
Because of their low elasticity modulus, titanium alloys have excellent biocompatibility, and are largely used in orthopedic prostheses. Among the properties that are beneficial for use in orthopedic implants is the elasticity modulus, which is closely connected to the crystal structure of the material. Interstitial elements, such as oxygen, change the mechanical properties of the material. Anelastic spectroscopy measurements are a powerful tool for the study of the interaction of these elements with the metallic matrix and substitutional solutes, providing information on the diffusion and concentration of interstitial elements. In this study, the effect of oxygen on the anelastic properties of alloys in the Ti-15Mo-Zr system was analyzed using anelastic spectroscopy measurements. The diffusion coefficients, pre-exponential factors, and activation energies of these alloys were calculated for oxygen.
Keywords: Diffusion; Ti Alloys; Interstitials; Biomaterials